Cross-Cultural Perspectives on Personhood and the Life Course - Degnen, Cathrine (Palgrave Macmillan US, 2018)
Exploring notions of the person through a wide range of anthropological literature, Cathrine Degnen analyses how personhood is built, affirmed, and maintained during various life stages and via multiple cultural forms and practices. In discussing the life course, she investigates personhood as a concept at the beginning of life, throughout life as lived, at the edges of being, and ultimately at life's end. Cross-Cultural Perspectives on Personhood and the Life Course moves beyond the human person in isolation to consider how personhood is fashioned with regard to place and how non-humans can also be recognised as persons. Through multiple ethnographic accounts, Degnen shows that personhood emerges as a relational and processual entity, brought into being via reciprocal fields of social relations.